The Copyright Pentalogy How the Supreme Court of Canada Shook the Foundations of Canadian Copyright Law - Geist, Michael (Law, Technology and Society, 2013)
The first comprehensive analysis of the July 2012 Supreme Court of Canada rulings on five copyright cases, this indispensible volume, edited by Michael Geist identifies the key aspects of the Court's decisions and considers the implications for the future of copyright law in Canada.